Triggers of different types of firm growth - Ponikvar, Nina (Economic and business review, 2022)
Authors define and explain firm growth as its transition from current position to short-term or long-term equilibrium motivated by profit maximisation. They allocate growing firms into six groups according to their growth type based on different dimensions of firm growth, i.e. growth of labour, growth of capital, growth of the volume of business, and growth of profit. Given that the typology of growing firms employed for the purpose of this paper is based on micro-economic theory, the triggers and their hypothesized relevance in explaining short-term and long-term growth patterns are also grounded in microeconomic theory. Accordingly, the authors study growth triggers in the form of the firm's technical and allocative (in)efficiency, its disequilibrium market position within a respective industry and the industry's market position relative to other industries. They thus assume that firm growth is either based on the utilization of firm's internal resources or is a result of favourable market conditions and hypothesize that the probability of a firm belonging to a particular type of growth is explained (i) with firm's internal efficiency, (ii) those market conditions that can be altered by the decisions adopted by management and (iii) those market conditions that are independent from the actions of management. The authors explore these triggers of three types of short-term growth, long-term growth, unsuccessful growth and downsizing, using data for 41,529 Slovenian firms in the 2007e2012 period. Results show that firm growth in Slovenia exhibits theoretically expected links between growth types and their triggers and also have relevant managerial implications.
Keywords: company performance; economic growth; ekonomska rast; enterprises; podjetje; poslovanje podjetja